International Logistics Criteria on Medicinal Products for Human Use - Meng, Shiang-Min; Yang, Hsiu-Yun; Dai, Jane (International Journal of Asian Social Science, 2019)
Medicinal products for human use relates to international logistics of pharmaceutical raw materials to the world people’s health and life, therefore international logistics provider plays an important part in order to ensure the stability of the quality of medicinal products. This study investigates international logistics provider to establish pharmaceutical industry outsourcing client satisfaction under international logistics criteria to confront with pharmaceutical good distribution practice (GDP) and good manufacturing practice (GMP) on medicinal products for human use. In the first phase, the international drug logistics criteria are referred from domestic and international GDP and GMP procedures and past literature review basis on outsourcing client logistics satisfaction. The second stage is the establishment of a standard questionnaire following the Delphi method. According to Delphi procedures, this study establishes logistics service criteria questionnaire items base on ten experts’ opinions and suggestions. After collecting the Delphi questionnaire, we realize the international logistics service provider lack the concept of the GDP logistics criteria, resulting in differences on the demand for logistics service. The logistics industry should take the initiative to pay attention to the GDP criteria that demand-side and supply-side consistency awareness in order to achieve the best logistics criteria. Through expert experience and specification to build a set of international logistics criteria for the pharmaceutical industry in order to provide international logistics provider to shorten or reduce the barriers to entering current international medicinal products for human use market to create high profit competitive environment.